Development of Byzantine Church Iconographic Programme: A Perspective from the Borderlands - Zakharova, Anna V. (Actual Problems of Theory and History of Art, 2019)
The paper summarizes the data resulting from the study of wall paintings in the cave churches of Cappadocia from the second half of the 9th to the early 11th century in order to reconstruct the process of shaping the classical system of Byzantine church decoration. The author singles out some Cappadocian ensembles showing Metropolitan influence: the churches Kılıçlar, El Nazar, New Tokalı in Göreme, Ala and Direkli in Belisirma, Kubelli and St. Barbara in Soğanlı, Tağar near Ürgüp and others. In the decoration of the domes, the apses, the vaults and the walls, we analyze those iconographic solutions that are different from the old schemes traditional for this region. In this respect, some cave churches imitating the Constantinopolitan cross-in-square churches are more indicative, although in some cases simpler structures also show the influence of Metropolitan iconography. Without going into details in the iconography of single subjects, we try to reveal the principles of shaping of these programs, in comparison with the fragments and descriptions of coeval ensembles in Constantinople and the Balkans.This comparative analysis allows us to get a more precise and detailed understanding of the formative process of Byzantine church decoration during the two centuries after Iconoclasm. Our research shows that this was a multistage process influenced by many different factors. The impulses from Constantinople were gradually assimilated and modified in the art of the Byzantine provinces, yet their artistic development went in the same direction as in the capital.
Keywords: Byzantine wall painting; Byzantine mosaics; Byzantine iconography; monumental church decoration; Cappadocia; Constantinople; Kılıçlar kilise; New Tokalı kilise; triconch in Tağar; the church of Stylianos Zaoutsas